1982
DOI: 10.1111/j.1095-8649.1982.tb02824.x
|View full text |Cite
|
Sign up to set email alerts
|

Food intake and growth of hybrid carp (female grass carp, Ctenopharyngodon idella× male bighead, Aristichthys (Hypophthalmichthys) nobilis) fed on zooplankton and Chara

Abstract: Food intake and growth of hybrid carp (female grass carp,Ctenopharyngodon idella x male bighead, Aristichthys (Hypophthalmichthys) nobilis) fed on zooplankton and CharaHybrid carp were raised in 165 1 indoor tanks. Two tanks were used in this study each stocked with five fish (average total length and weight=235.7 mm; 116.1 g); one tank was provided with zooplankton and the other with zooplankton and Cham sp. The hybrids fed actively on zooplankton at an average daily rate of 39% and Chum at 2.6% by body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Hybrids grew very slowly (0.1 g d-l), and consumption was thought to be near maintenance level. Similarly, consumption rates of 30-45% body weight d -1 have been reported by others (Kilambi and Zdinak, 1982;Harberg and Modde, 1985). Beaty et al, (1983a) reported that hybrid grass carp were successful in reducing vegetation growth while temperatures remained high, but surgically sterilized grass carp consumed significantly more vegetation than hybrids of the same size.…”
Section: Efficiency Of Hybrids In Vegetation Controlsupporting
confidence: 60%
“…Hybrids grew very slowly (0.1 g d-l), and consumption was thought to be near maintenance level. Similarly, consumption rates of 30-45% body weight d -1 have been reported by others (Kilambi and Zdinak, 1982;Harberg and Modde, 1985). Beaty et al, (1983a) reported that hybrid grass carp were successful in reducing vegetation growth while temperatures remained high, but surgically sterilized grass carp consumed significantly more vegetation than hybrids of the same size.…”
Section: Efficiency Of Hybrids In Vegetation Controlsupporting
confidence: 60%
“…The daily growth rates in the current experiment were (0.46, 0.52, 0.60, and 0.95) g/day for T1, T2, T3, and T4, respectively. 22 recorded a daily growth rate of 0.43 g/day for the hybrid grass carp cultured under laboratory conditions and fed on zooplankton and phytoplankton. The results of the current study differed from those of 23 who used aquatic and terrestrial plants to feed grass carp for five months, where the daily growth rate ranged between 1.67-2.91 g/day.…”
Section: Discussionmentioning
confidence: 99%